Detecting Fraudulent Financial Reporting Using Fraud Score Model and Fraud Pentagon Theory : Empirical Study of Companies Listed in the LQ 45 Index - Naomi Clara Situngkir; Dedik Nur Triyanto (The Indonesian Journal of Accounting Research, 2020)
Misstatements and concealment of facts about the value of accounts in the financial statements indicate a fraudulent financial reporting. As a result, financial information is irrelevant and misleading. The purpose of this study was to analyze the fraud pentagon theory in detecting fraudulent financial reporting using the fraud score model of companies listed in the LQ 45 index on the Indonesia Stock Exchange in 2014-2018. The results showed financial stability, external pressure, nature of the industry, effective monitoring, change in auditors, total accruals, change in directors, the proportion of independent commissioners, frequent numbers of CEO's picture and family firms simultaneously affect the fraudulent financial reporting. Partially, financial stability and Family firms have a positive effect, external pressure and total accruals have a negative effect, and the nature of industry, effective monitoring, change in auditors, change in director, the proportion of independent commissioners, and frequent number of CEO's picture have no effect on fraudulent financial reporting. Based on the results of the research, fraud pentagon theory can be used to minimize the occurrence of fraudulent financial reporting that may be done by the company by ensuring the fairness of a financial report and assessing the risk of fraud by taking into account all aspects, especially on asset change ratios, debt ratios, accounts receivable ratios, percentage of independent audit committees change in auditors, changes in directors.